States of Exile and Marginalization. Issue 3 (4th May 2018) - Straker, Gillian
Abstract : The experience of marginality is visceral. The artist Tracey Moffatt, Australia's representative at the 2017 Vienna biennale, understands this exquisitely. Her work depicts marginality and states of exile powerfully and compels us to respond. In speaking to the traumatic images in her work I am aware that words are inadequate. The Lacanian Real of trauma is always an excess, the beyond of words. This is recognized by Moffatt in her largely wordless work, which nevertheless speaks to many states of exile engendered by geographical isolation, cultural domination and hybridity, powerlessness, and dependence, as well as alienated states produced by everyday misattunements.